07Jan

Найдите сумму всех корней уравнения (x−1/x^3+3*x^2+x+3)+(1/x^4−1)=(x+1/x^3+3*x^2−x−3).

disar Алгебра 1 5

Найдите сумму всех корней уравнения (x−1/x^3+3*x^2+x+3)+(1/x^4−1)=(x+1/x^3+3*x^2−x−3).

Posted by disar | Posted at Jan 07, 2014 | Categories: Алгебра

Answers

Александра00
Александра00

[latex]frac{x-1}{x^3+3*x^2+x+3}+ frac{1}{x^4-1}= frac{x+1}{x^3+3*x^2-x-3}[/latex] [latex]frac{x-1}{x(x^2+1)+3(x^2+1)}+ frac{1}{(x^2-1)(x^2+1)}= frac{x+1}{x(x^2-1)+3(*x^2+1)}[/latex] [latex]frac{x-1}{(x+3)(x^2+1)}+ frac{1}{(x^2-1)(x^2+1)}= frac{x+1}{(x+3)(x^2-1)}[/latex] [latex]frac{(x-1)(x^2-1)+x+3-(x+1)(x^2+1)}{(x+3)(x^2+1)(x^2-1)}=0[/latex] [latex]frac{x^3-x-x^2+1+x+3-x^3-x-x^2-1}{(x+3)(x^2+1)(x^2-1)}=0[/latex] [latex]frac{-x-2x^2+3}{(x+3)(x^2+1)(x^2-1)}=0[/latex] [latex]frac{-2(x-1)(x-1,5)}{(x+3)(x^2+1)(x^2-1)}=0[/latex] [latex]x_1=1[/latex]∈ОДЗ [latex]x_2=1,5[/latex] Ответ: 1,5

Jan 07, 2014 12:55

Leave a answer